The Library of a Madrasa in Aleppo at the End of the Ottoman Era: The Renewed Register of the Books Endowed by Uthman Pasha al-Duriki - Aljoumani, Said (Ergon-Verlag, 2020)
This study provides a unique insight into the book culture of Aleppo in the 19th century. The document at the heart of this book is the ‘renewed register of the books endowed by ʿUthmān Pāshā’. This register allows a new perspective on what subjects were taught in madrasas and what subjects such a madrasa library covered. Among its over 1200 titles we find a variety of different subjects, most importantly those concerned with the transmitted fields of knowledge. Yet, this document also sheds light on the day-to-day working of the library as it sets out the job description of the librarian, the intended audience as well as the usage conditions in previous book endowments. In a second part, this study follows the 20th-century trajectory of the books that once sat on the shelves of this library. Most importantly, it succeeds in identifying for almost half of the titles the actual manuscript among the holdings of the Syrian National Library in Damascus.